Ring-Closing Metathesis and Ring-Opening Metathesis Polymerization toward Main-Chain Ferrocene-Containing Polymers - Sha, Ye; Zhang, Yudi; Zhu, Tianyu; Tan, Shaobo; Cha, Yujin; Craig, Stephen L; Tang, Chuanbing (Macromolecules, 2018)
We report the preparation of cyclic ferrocenyl olefins with various substituents and different ring sizes by ring-closing metathesis (RCM). These ferrocene-containing monomers were subject to ring-opening metathesis polymerization (ROMP), leading to main-chain ferrocene-containing homopolymers, random copolymers, and block copolymers. Depending on the substituents, ferrocenyl homopolymers are semicrystalline or amorphous with good solubility. A semicrystalline polymer was used in the crystallization-driven self-assembly (CDSA) of block copolymers to generate platelet nanostructures.